The cactus and snowflake at work : how the logical and sensitive can thrive side by side - Zack, Devora (Berrett-Koehler Publishers, Inc., 2021)
"Feelers (those who lead with their hearts) and Thinkers (those who lead with their heads) can combine their strengths and work together if they follow the sage advice in this playful but practical guide. This book shows how people who "melt" (snowflakes) and people who retain their heat (cacti) when the temperatures rise at work can meet in the middle and combine their strengths in the workplace"--